Consumo simbólico da moda de luxo: signos e discursos midiatizados pela Gucci na gestão de Alessandro Michele - Abib, Tamíris Idalgo (2024)
This dissertation delves into the sophisticated communication strategies employed by the luxury market to substantiate its exclusivity while distancing itself from perceptions of frivolity. Focused on Gucci's recent advertising campaigns, the study aims to unravel the main discourses and meanings that underpin the brand's production logics. Central to the investigation is the exploration of how Gucci constructs a symbolic consumption experience through the mediation of signs and discourses, transcending the mere utility of its products. The analysis hones in on the symbols and speeches prevalent in Gucci's 2022 advertising, coinciding with Creative Director Alessandro Michele's final year in charge. Adopting a hybrid methodology that integrates semiotic assumptions and French discourse analysis, specifically the concept of interdiscourse, the research seeks to map the intricate web of meanings embedded in the brand's communication strategies. By deciphering these discourses, the study aims to uncover the essence of symbolic consumption in the luxury market and illuminate the nuanced motivations beyond the pursuit of mere opulence or distinction.